Direct observation in a large-scale randomized trial of parent training in children with autism spectrum disorder and disruptive behavior. (November 2021) - Swiezy, Naomi; Smith, Tristam; Johnson, Cindy R.; Bearss, Karen; Lecavalier, Luc; Drill, Rochelle; Warner, Danielle; Deng, Yanhong; Xu, Yunshan; Dziura, James; Handen, Ben; Scahill, Lawrence
Highlights: Lessons learned from using a direct observation strategy (i.e., SOAP) in the evaluation of child and parent behavior as part of the largest randomized trial of behavior intervention in ASD to date. Despite meeting criteria for the study, child participants did not demonstrate appreciable levels of behavior at baseline on the SOAP. Significant effort and resources were subsumed in training, coding and otherwise utilizing the measure across sites. Study results give rise to considering the suitability (i.e., feasibility, practicality, risk-benefit) of using direct observation as a primary outcome measure for larger scale randomized control trials. Abstract: A direct observation strategy (Standardized Observation Analogue Procedure, SOAP) was used in a large-scale randomized trial of parent training versus parent education in young children with autism spectrum disorder (ASD) and disruptive behavior. The 16-minute SOAP, modified from an earlier version of this same measure, included parentchild interaction to assess child behavior in a clinical laboratory setting. Despite study entry criteria for all child participants requiring moderate levels of disruptive behavior in this project, 126 of 168 children with complete SOAP data at baseline showed no disruptive behavior on this measure. Although the primary purpose of the study was to determine whether the SOAP could detect differences between the two conditions (i.e., parent training (PT) and parent education (PE)), baseline observation data was not consistent with parent ratings at baseline or subsequent follow up visits, leaving little room to demonstrate improvement with this observation measure. This and the challenging, time-consuming and resource intensive effort involved in using such a measure in a large randomized scale trial, raises fundamental questions about the validity of the SOAP as an outcome measure in such a study. Further consideration related to the feasibility and practicality of using direct observation as a primary measure in larger scale efforts overall are also discussed.